2014
DOI: 10.2459/jcm.0000000000000050
|View full text |Cite
|
Sign up to set email alerts
|

Why is functional capacity decreased in hypertensive patients? From mechanisms to clinical studies

Abstract: The influence of arterial hypertension on functional capacity is poorly understood. Studies have shown that peak oxygen consumption has been reduced in hypertensive patients, but the mechanisms are unclear. Left ventricular systolic and diastolic dysfunction, as well as left ventricular hypertrophy, are associated with lower functional capacity in patients with arterial hypertension. Furthermore, some investigations found a significant relationship between right ventricular systolic function and functional cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 92 publications
1
10
0
Order By: Relevance
“…Moreover, reverse BP dipping pattern was positively associated with increased ventilation/carbon dioxide. This might be explained by changes in pulmonary vasculature and cardiac dysfunction induced by arterial hypertension . Studies showed that ventilation/carbon dioxide slope was the strongest predictor of mortality and severe complications after lung resection, and superior predictor to the oxygen uptake efficiency slope in patients with heart failure …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, reverse BP dipping pattern was positively associated with increased ventilation/carbon dioxide. This might be explained by changes in pulmonary vasculature and cardiac dysfunction induced by arterial hypertension . Studies showed that ventilation/carbon dioxide slope was the strongest predictor of mortality and severe complications after lung resection, and superior predictor to the oxygen uptake efficiency slope in patients with heart failure …”
Section: Discussionmentioning
confidence: 99%
“…This might be explained by changes in pulmonary vasculature and cardiac dysfunction induced by arterial hypertension. 5 Studies showed that ventilation/carbon dioxide slope was the strongest predictor of mortality and severe complications after lung resection, 21 and superior predictor to the oxygen uptake efficiency slope in patients with heart failure. 22 TA B L E 4 The association between demographic and clinical with parameters of cardiopulmonary exercise testing (correlation and multivariate regression analyses)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only recently have the studies that investigate RV mechanics in hypertensive patients appeared. They have shown significant deterioration of RV longitudinal deformation and revealed the association between RV longitudinal strain and functional capacity in hypertensive patients . Furthermore, the studies have detected that RV longitudinal strain represents the strongest independent predictor of RV function, as well as the strong relationship between RV longitudinal strain and cardiovascular mortality and morbidity in a wide range of cardiovascular conditions …”
Section: Introductionmentioning
confidence: 98%
“…They have shown significant deterioration of RV longitudinal deformation [8][9][10][11] and revealed the association between RV longitudinal strain and functional capacity in hypertensive patients. 12,13 Furthermore, the studies have detected that RV longitudinal strain represents the strongest independent predictor of RV function, 14 as well as the strong relationship between RV longitudinal strain and cardiovascular mortality and morbidity in a wide range of cardiovascular conditions. 15,16 The purpose of this review article is to provide the overview of the current knowledge regarding the role of RV structure, function, and particularly mechanics in hypertensive population.…”
Section: Introductionmentioning
confidence: 99%